Ontogenetic development of cardiac tolerance to oxygen deprivation - possible mechanisms - Ošťádal, Bohuslav; Ošťádalová, Ivana; Kolář, František; Charvátová, Zuzana; Netuka, Ivan (Physiological research, 2009)
Our present focus on the hypoxic immature heart is driven by clinical urgency: cyanotic congenital cardiac malformations remain the single largest cause of mortality from congenital defects and ischemic heart disease is no more the disease of the fifth and older decades but its origin as well as risk factors are present already during early ontogeny. Moreover, the number of adult patients operated for cyanotic congenital heart disease during infancy steadily increases. This group approaches the age of the rising risk of serious cardiovascular diseases, particularly ischemic heart disease. Experimental results have clearly shown that the immature heart is significantly more tolerant to oxygen deficiency than the adult myocardium. However, the mechanisms of this difference have not yet been satisfactorily clarified; they are likely the result of developmental changes in cardiac energy metabolism, including mitochondrial function. The high resistance of the newborn heart cannot be further increased by ischemic preconditioning or adaptation to chronic hypoxia; these protective mechanisms appear only with decreasing tolerance during development. Resistance of the adult myocardium to acute oxygen deprivation may be significantly influenced by perinatal hypoxia. These results suggest that the developmental approach offers new possibilities in the studies of pathogenesis, prevention and therapy of critical cardiovascular diseases.
Keywords: Male; zvířata; Mitochondria, Heart; hypoxie; Animals; srdeční mitochondrie; sexuální faktory; Energy Metabolism; Heart; ženské pohlaví; ischemické přivykání; myokard; Oxygen; energetický metabolismus; Myocardium; kyslík; Cardiovascular Diseases; Humans; Age Factors; Hypoxia; Sex Factors; Financing, Organized; kardiovaskulární nemoci; Female; Adaptation, Physiological; mužské pohlaví; fyziologická adaptace; financování organizované; lidé; srdce; věkové faktory; Ischemic Preconditioning, Myocardial